Analisis Sistem Ergonomi Terhadap Stasiun Kerja Komputer di CV. Sri Lestari - May Setiawan; Farid Wajdi (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2016)
This study aims to design a computer workstation that can be adjusted for employees to provide convenience and comfort in work. Data collection is done on employees at CV. Sri Lestari includes anthropometry of employee bodies and anthropometry of computer desks and chairs with direct measurement methods using a measuring ruler. The data obtained was carried out uniformity test, data adequacy test and percentile calculation and then the comfortable table-chair design were carried out for CV employees. Sri Lestari. The method used in this design is the anthropometry approach. The anthropometric approach is used to determine the dimensions of a computer workstation. Percentile 5 is used to identify aspects related to range, while 95th percentile is to determine dimensions about the dimensions of space. The results showed that from a comparison of sizes, computer tables that exist today regarding extent are sufficient by the user anthropometry and appropriate for the minimum needs of a computer desk for employees of CV. Sri Lestari. It's just that the size of the computer chair needs to be considered. If this is necessary to adjust the computer chair. The design of a computer workstation that can be modified can provide convenience and comfort for employees at work. The ability to adopt a product is a fundamental requirement in the design process.